Pengembangan Microlearning Content Melalui Media Sosial Sebagai Sumber Belajar Vocabulary Secara Mandiri Siswa Sekolah Menengah Kejuruan - Erwana Erwana; Nurhikmah Nurhikmah; Abdul Hakim (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
The integration of information and communication technology in education has encouraged the development of innovative learning resources that are relevant to the characteristics of today's digital generation. Social media platforms such as TikTok, Instagram, and YouTube offer opportunities to support independent English vocabulary learning through microlearning content. This study aimed to analyze the need for developing microlearning content through social media as an independent vocabulary learning resource for vocational high school students. The study employed a quantitative descriptive design involving 30 vocational high school students and English teachers selected through purposive sampling. Data were collected using Likert-scale questionnaires and analyzed descriptively with SPSS. Instrument testing indicated that 19 of 20 questionnaire items were valid, while the reliability test produced a Cronbach's Alpha value of 0.922, indicating excellent reliability. The findings revealed that students still experienced difficulties in mastering English vocabulary and required more flexible, attractive, and accessible learning resources. Students also showed positive responses toward short, visual, and interactive learning content delivered through social media, which was perceived to support learning motivation and self-regulated learning. These findings indicate that developing microlearning content through social media is both relevant and feasible as an innovative vocabulary learning resource for vocational high school students. The results provide a basis for designing digital learning resources that are aligned with students' learning characteristics and the demands of technology-enhanced education.